2019
DOI: 10.1111/mec.15033
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic disturbance affects aquatic microbial community composition and food web interactions but not community resilience

Abstract: Notwithstanding the fundamental role that environmental microbes play for ecosystem functioning, data on how microbes react to disturbances are still scarce, and most factors that confer stability to microbial communities are unknown. In this context, antibiotic discharge into the environment is considered a worldwide threat for ecosystems with potential risks to human health. We therefore tested resilience of microbial communities challenged by the presence of an antibiotic. In a continuous culture experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…For example, antibiotic pollution in aquatic environments was found to reduce overall microbial diversity, including taxa responsible for carbon cycling and primary productivity [146,166,167,168]. Similarly, the presence of antibiotics in soil was found to alter microbial community structure, leading to a loss of biomass and a reduction in microbial activity including nitrification, denitrification, and respiration [169,170,171].…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%
“…For example, antibiotic pollution in aquatic environments was found to reduce overall microbial diversity, including taxa responsible for carbon cycling and primary productivity [146,166,167,168]. Similarly, the presence of antibiotics in soil was found to alter microbial community structure, leading to a loss of biomass and a reduction in microbial activity including nitrification, denitrification, and respiration [169,170,171].…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%
“…(15) Ecotoxicological modelling according to USEtox, damage to the ecosystem from increased AB concentrations in the environment is characterized as freshwater ecotoxicity impacts. (16) Weak evidence for damage to ecosystem from ABR (Eckert et al 2019). ( 17 Szumilas (2010, p227) as the representation of "the chance that an outcome will occur given a particular exposure compared to the odds of the outcome occurring in the absence of that exposure".…”
Section: Approach 2: Characterizing Human Health Impacts For Abr (Endpoint)mentioning
confidence: 99%
“…(15) Ecotoxicological modelling according to USEtox, damage to the ecosystem from increased AB concentrations in the environment is characterized as freshwater ecotoxicity impacts. (16) Weak evidence for damage to ecosystem from ABR(Eckert et al 2019). (17) End-point measurement of ecotoxicological effects, no clear ecosystem effect from ABR…”
mentioning
confidence: 99%
“…While on one hand these bacteria are known to not be competitive in such environments and to be grazed easily when entering freshwaters through faecal pollution (i.e. (González, et al 1992;Eckert, et al 2019)), the evolution of freshwater E. coli (Touchon, et al 2020) and renaturation of these bacteria have been observed (Ishii, Ksoll, et al 2006;Ishii and Sadowsky 2008), showing that at least part of the incoming E. coli must survive over longer time periods in water. In a previous study we found that lake zooplankton could show remarkable quantities of E. coli related 16S rRNA gene sequences and we confirmed this here by quantifying the abundance of uidA gene, an unambiguous indicator for E. coli presence (Figure 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, pelagic cold waters are a very hostile environment for such gut symbionts. If they are not grazed by flagellated predators upon arrival, they are surely not favoured by resource competition (González, et al 1992;Wanjugi and Harwood 2013;Eckert, et al 2019). Since evolution, as seen in the genome reduction of E. coli (Touchnon, et al 2020), takes time, a certain long-term persistence of vertebrate commensal strains in the aquatic habitat is crucial, and the question remains: In which niche does persistence take place?…”
Section: Introductionmentioning
confidence: 99%